Precoded generalised frequency division multiplexing system to combat inter‐carrier interference: performance analysis. Issue 15 (1st October 2015) - Tiwari, Shashank; Sekhar Das, Suvra; Bandyopadhyay, Kalyan Kumar
Abstract : The expected operating scenarios of fifth‐generation (5G) pose a great challenge to orthogonal frequency division multiplexing which has poor out of band spectral properties, stringent synchronisation requirements and large symbol duration. Generalised frequency division multiplexing (GFDM) which is the focus of this work has been suggested in the literature as one of the possible solutions to meet 5G requirements. In this study, the analytical performance evaluation of minimum mean square error (MMSE) receiver for GFDM is presented. The authors also proposed precoding techniques to enhance the performance of GFDM. A simplified expression of signal‐to‐interference and noise ratio (SINR) for MMSE receiver of GFDM is derived using special properties related to the modulation matrix of GFDM, which are described in this study. This SINR is used to evaluate the bit error rate performance. Precoding schemes are proposed to reduce complexity of GFDM–MMSE receiver without compromising on the performance. Block inverse discrete Fourier transform (BIDFT) and discrete Fourier transform (DFT)‐based precoding schemes are found to outperform GFDM–MMSE receiver due to frequency diversity gain while having complexity similar to zero‐forcing receiver of GFDM. It is shown that both BIDFT‐ and DFT‐based precoding schemes reduce peak‐to‐average power ratio significantly. Computational complexities of different transmitters and receivers of precoded and uncoded GFDM are also presented.